Experimental Music in Black and White: The AACM in New York, 1970-1985 - Lewis, George E. (Current Musicology, 2001)
Since its founding on the virtually all-black South Side of Chicago in 1965, the African American musicians’ collective known as the Association for the Advancement of Creative Musicians (AACM) has played an unusually prominent role in the development of American experimental music. The composite output of AACM members explores a wide range of methodologies, processes, and media. AACM musicians have developed new ideas about timbre, sound, collectivity, extended technique and instrumentation, performance practice, intermedia, the relationship of improvisation to composition, form, scores, computer music technologies, invented acoustic instruments, installations, and kinetic sculptures. In a 1973 article, two early AACM members, trumpeter John Shenoy Jackson and co-founder and pianist/composer Muhal Richard Abrams, asserted that, “The AACM intends to show how the disadvantaged and the disenfranchised can come together and determine their own strategies for political and economic freedom, thereby determining their own destinies” (Abrams and Jackson 1973:72). This optimistic declaration, based on notions of self-help as fundamental to racial uplift, cultural preservation, and spiritual rebirth, was in accord with many other challenges to traditional notions of order and authority that emerged in the wake of the Black Power Movement.